Implantable Bioresponsive Hydrogel Prevents Local Recurrence of Breast Cancer by Enhancing Radiosensitivity - Fu, Zhiguang; Li, Hongqi; Xue, Peng; Yu, Hanying; Yang, Shuo; Tao, Cheng; Li, Wei; Wang, Yingjie; Zhang, Jianjun; Wang, Yu (Frontiers in Bioengineering and Biotechnology, 2022)
Breast cancer is one of the most common types of cancer. Patients are often concerned about regional recurrence after breast cancer surgery. Radiotherapy plays a vital role in reducing recurrence and prolonging the survival of patients undergoing breast-conserving surgery and high-risk mastectomy. However, 8-15% of patients still have disease progression due to radiation resistance. Therefore, new strategies for combination radiotherapy sensitization must be investigated. In this study, an implantable drug loading system, sunitinib nanoparticles @ matrix metalloproteinases -response hydrogel (NSMRH), uses enzyme-sensitive hydrogel as a carrier to load sunitinib nanoparticles, was identified. The releasing profile demonstrated that sunitinib nanoparticles may be continuously released from the hydrogels. Functional experiments revealed that, when paired with NSMRH, radiation may significantly inhibit tumor cell proliferation, migration, and invasion in vitro. Further animal experiments showed that NSMRH combined with radiotherapy could more effectively control the recurrence of subcutaneous xenograft tumors, prolong the survival time, and have no obvious toxicity in nude mice. Finally, by studying the molecular mechanism of NSMRH, it was hypothesized that in breast cancer cells, NSMRH cooperated with sensitized radiotherapy, mainly due to significantly blocking the G2/M phase, reducing the DNA repair efficiency, inhibiting tumor angiogenesis, promoting apoptosis, and reversing the abnormal expression of platelet-derived growth factor receptor alpha (PDGFRA) after radiotherapy. These findings suggest that NSMRH's radiation sensitization and anti-tumor activity may aid in the development of a novel method in future clinical applications.